Laboratory investigation for development of local scour depth model for varying shapes of obstruction. (13th September 2019) - Mir, Bintul Huda; Lone, Mohd Akbar; Bhat, Javaid Ahmad
This paper reports the effect of the shape of obstruction on local scour depth. Laboratory experiments were conducted on a tilting glass flume to study scour phenomenon around five obstructions of different shapes. Obstructions studied were chosen keeping in view not only the bridge piers but also some other structures, like obstructions in the flow channels, e.g., a jetty, big boulder, any building in the coastal area, etc. Maximum local equilibrium scour, a dependent parameter, was studied as a function of flow parameters and shape parameters of the obstruction. A model was developed for the maximum local scour depth estimation in which maximum local scour depth ( ds ) is a function of Froude number ( Fr ), flow depth ( y ) and shape factor ( Sf ). The experimental findings depict a considerable effect of the shape of obstruction on the local scour depth.